Análisis comparativo de dos calentadores solares de diferente tipo de construcción para las condiciones climatológicas y aplicaciones en la ciudad de Loja. - Vásquez Espinosa, Mario Antonio (2023)
The present investigation emphasizes the thermal evaluation of two solar heaters of flat plate of different type of construction with 1.44 m^2of effective collection area. In the part experimentally, the flat plate solar collectors of the Faculty of Energy, Industries are used and the Non-Renewable Natural Resources of the National University of Loja, in which through The implementation of a thermal measurement system in each collector allows the collection of water temperature data at the inlet of the collector, water temperature at the outlet of the collector, absorber plate temperature, glass cover temperature, temperature water inside the tank, ambient temperature and relative humidity; Additionally, the data of wind speed and solar radiation were obtained from Meteorological Station 50001- Faculty of Energy. During the monitoring period under the weather conditions of the city of Loja had sunny, combined (sunny-cloudy) and cloudy days, where for the month July it was obtained that the efficiency of the collector with an absorber plate of copper tubes arranged to the aluminum fins is 2.74% higher than the efficiency of the collector with an absorber plate galvanized zinc with copper tubes fitted to the collection plate. Based on this study It can be stated that in warm temperate climates the construction topology of an absorbent plate of copper tubes fixed to aluminum fins is more advantageous for the purposes of absorbed heat and thermal efficiency Keywords: energy balance, solar collector, thermal measurement system, thermal efficiency, optical efficiency.